Modifications of volume, shape and structure during metamorphism: Unearthing some ignored strain paths. (August 2015) - Guzzetta, Giuseppe; Rebay, Gisella
Abstract: A deformational process – that is the joint transformation of volume, shape and structure of a continuum playing the role of an actual material – can be described as a transformation of a vector space. Using such description one may notice that there are some cases of homogeneous deformation the very existence of which is usually ignored. It is suggested here that the recognition of these additional cases is a prerequisite for a fully comprehensive consideration and interpretation of tectonic fabrics, and a constructive reassessment of basic concepts of continuum mechanics. Highlights: Describing homogeneous deformation as a transformation of a vector space, all possible strain paths are recognizable. The very existence of some of them cannot be justified without taking into account couple stresses. That is a prerequisite to read the record of the deformational history in metamorphic rocks.